In Vivo Characterization of a New Synthetic Thrombin Inhibitor - Knabb, Robert M; Kettner, Charles A; Timmermans, Pieter B M W M; Reilly, Thomas M (Thrombosis and Haemostasis, 1992)
We have examined the in vivo pharmacology of DuP 714 (Ac-[D]-Phe-Pro-boroArginine), a representative of a new series of synthetic thrombin inhibitors which contain a boronic acid derivative of arginine. Intravenous bolus injections of DuP 714 in anesthetized rats and conscious rabbits produced transient elevations of clotting times. Clinically relevant prolongations of the APTT were also observed in rabbits after i. v. infusion of less than 0.1 mg kg-1 h-1. Efficacy against venous thrombosis was demonstrated in a rabbit model of stasis induced thrombosis. Clots formed in 100% of control animals and only 33% of animals treated with 0.5 mg/kg DuP 714, and were less severe in treated animals. In a rabbit arterial-venous shunt model mimicking arterial thrombosis, occlusion occurred within 30 min in 72% of control animals vs. 11% of animals treated with 0.1 mg kg-1 h-1 DuP 714. Results indicate that DuP 714 is a highly effective anticoagulant which should be useful for the prevention of both venous and arterial thrombotic diseases.